2023
DOI: 10.3390/s23063201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensing Tactile Arrays, Shear Force, and Proprioception of Robot on Texture Recognition

Abstract: In robotics, tactile perception is important for fine control using robot grippers and hands. To effectively incorporate tactile perception in robots, it is essential to understand how humans use mechanoreceptors and proprioceptors to perceive texture. Thus, our study aimed to investigate the impact of tactile sensor arrays, shear force, and the positional information of the robot’s end effector on its ability to recognize texture. A deep learning network was employed to classify tactile data from 24 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The integration of our texture and Vel_Pro f classifiers into a combined tactile system is a logical future step for this work. Prior studies have demonstrated how combining both proprioceptive and tactile senses using Neural Networks (NNs) generally leads to an increase in texture classification performance [22,28]. Alternative approaches using reservoir computing paradigms could also be explored due to their largely interconnected neuronal structure mimicking areas of the brain [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of our texture and Vel_Pro f classifiers into a combined tactile system is a logical future step for this work. Prior studies have demonstrated how combining both proprioceptive and tactile senses using Neural Networks (NNs) generally leads to an increase in texture classification performance [22,28]. Alternative approaches using reservoir computing paradigms could also be explored due to their largely interconnected neuronal structure mimicking areas of the brain [55].…”
Section: Discussionmentioning
confidence: 99%
“…This methodology creates detailed tactile images of the texture surface but does not examine the surface during movement or the application shear forces, an important effect during tactile interactions that we seek to investigate here. Yang et al [22] highlights the importance of these shear forces when identifying texture using tactile sensors.…”
Section: Related Workmentioning
confidence: 99%
“…Referring to this standard, as shown in Figure 8, the SNR dropped below 20 dB after 500 scans for λ = 1 mm, whereas the SNR remained above 20 dB even after 1000 scans for λ = 2 mm. One potential application of the tactile texture sensor is the autonomous classification of textures [43][44][45]. Therefore, the necessary sensitivity levels should be discussed in the context of textural classification in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the Information Era, data acquisition and processing are inseparable from the participation of sensors. They are widely used in robotics [ 2 , 3 , 4 , 5 ], motion monitoring [ 6 , 7 , 8 , 9 ], medical, human–machine interaction [ 10 ], and other fields [ 11 , 12 , 13 ]. However, traditional tactile sensors rely on external power sources for their power supply, which can lead to problems such as large system size, high cost, and difficult maintenance.…”
Section: Introductionmentioning
confidence: 99%